2014
DOI: 10.1007/s00059-014-4187-x
|View full text |Cite
|
Sign up to set email alerts
|

Echo-guided pericardiocentesis in patients with clinically significant pericardial effusion

Abstract: Echo-guided pericardiocentesis has a high success and low complication rate in current practice. Among etiologies, malignancy remains the most common cause of clinically significant pericardial effusion and is associated with a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…(1,7) Consistent with other series, patients with malignant pericardial effusions have a poor prognosis with typical median survival of 3-7 months. (3)(4)(5)7) This is consistent with the 45.0% survival rate at 12 months in our patients. However, patients presenting with haemopericardium due to acute ascending aortic syndrome, which consists of aortic dissections or rupture of aortic aneurysms, and free wall myocardial rupture had the worst shortterm prognosis despite undergoing emergent surgery.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…(1,7) Consistent with other series, patients with malignant pericardial effusions have a poor prognosis with typical median survival of 3-7 months. (3)(4)(5)7) This is consistent with the 45.0% survival rate at 12 months in our patients. However, patients presenting with haemopericardium due to acute ascending aortic syndrome, which consists of aortic dissections or rupture of aortic aneurysms, and free wall myocardial rupture had the worst shortterm prognosis despite undergoing emergent surgery.…”
Section: Discussionsupporting
confidence: 92%
“…(2) Conversely, in advanced countries, complications of cardiac surgery and cancer are the most common causes. (3)(4)(5) Furthermore, the proportions of pericardial effusions caused by malignancy and postsurgical complications may be increasing over time, in part due to improved survival among cancer patients and the increasing number of cardiac interventions in developed countries. (6) The prognosis of pericardial effusion is essentially related to its aetiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may represent a racial disparity rather than a chance finding, and will need to be explored in the future studies . Also, the high risk of in‐hospital mortality in acute myocardial infarction with moderate or large pericardial effusion is well known, and is mostly attributed to cardiac rupture . Malignancy was another important predictor of inpatient mortality in ouranalysis.…”
Section: Discussionmentioning
confidence: 84%
“…Vayre et al 8 chose the subxiphoid approach for most of his case series and reported a complication rate of 21% (0.9% major and 20.1% minor). Akyuz et al 9 reported the use of the subcostal (85%) and apical approach (15%) under echocardiographic guidance, and reported a complication rate of 1.3% for all minor and major complications.…”
Section: Discussionmentioning
confidence: 99%